Who becomes a Special Guardian: What we can learn from linked data - Bennett, Verity; Warner, Nell; Stabler, Lorna (International Journal of Population Data Science, 2025)
Objectives A Special Guardianship Order (SGO) is a court order that makes somebody other than a child’s parents their legal guardian. However very little is known about who becomes a Special Guardian, or who children live with following an SGO, and those people’s health and other characteristics. Methods Data from Children and Family Court Advisory and Support Service held in the SAIL databank, were used to identify children who had received SGOs in Wales and where possible who the SGOs were granted to. This data was linked to the Welsh Demographic Service Data to identify the households that children were living in following an SGO, and area level deprivation. Linkage to health datasets enabled the identification of health characteristics. The households of children with an SGO were compared with households in the rest of the population. Results Adults in households with SGOs were more likely than comparison households to be older, live in areas of deprivation and have certain medical conditions, including anxiety and depression. Conclusion The findings highlight differences between populations that may need additional support from service providers.